Postawy narodowe adwokatów górnośląskich w okresie II wojny światowej - Krzyżanowski, Lech (Wydawnictwo Uniwersytetu Wrocławskiego, 2013)
At the time of the commencement of the Second World War, the Upper Silesian circle of attorneys was of a uniformly Polish national structure. Nevertheless, during the occupation many lawyers took decisions which may theoretically be assessed as questionable from the national standpoint. It concerned both attorneys who found themselves on the territory of the General Government and lawyers who remained in Upper Silesia. The former gained possibility to continue their legal practice, though at the price of accepting German supervision over their work, whereas the lawyers who did not leave Upper Silesia faced the necessity of applying for a registration on the German national list. The majorities of both groups of Upper Silesian lawyers decided to accept the conditions established by the occupant. However, it did not translate into automatic renunciation of Polish national feelings. Most often the decision to accept the German national list was caused by the threat of imprisonment in concentration camp; many times it was the only way to secure a minimum level of material existence. In turn, the work in the official justice system created an opportunity to help the Polish population and many lawyers engaged in such work made a full use of this opportunity, justifying in this way their coerced cooperation with the Germans. After the end of the Second World War the verification procedure was conducted in Katowice chamber during which the accusations of accepting the German national list or of working in the legal judiciary were levelled against attorneys. All trials ended with pronouncing the accused as innocent; these sentences were not questioned during later years. It provides a strong evidence of the social understanding of the national attitudes of Upper Silesian attorneys. Especially, it should not be forgotten that the majority of them did not experience any ambiguities over their national allegiance and that many of them exhibited their patriotism by serving in underground organizations or in the Polish military.
Keywords: adwokaci; Górny Śląsk; II wojna światowa